Społeczna odpowiedzialność biznesu jako element budowania przewagi konkurencyjnej - najlepsza praktyka biznesowa Grupy Maspex Wadowice - Gapska, Katarzyna; Ocieka, Barbara (The Role of Corporate Social Responsibility in the Creation of Competitive Advantage - Best Practice Case of Maspex Wadowice Group, 2009)
The article presents considerations of both authors regarding best business practices. The basis for analysis are their own literature studies and empirical research. In the first part, different approaches to the definition of best business practice and its specific characteristics are analysed. The presented concept regards business solutions which include three integrated dimensions: economic, environmental and social. The second part constitutes the description of empirical research done with Maspex Wadowice Group, the leading juice producer in Poland. The company decided to implement new production technology (aseptic production) which aim was not only to optimise costs, but also to strengthen social responsibility policy. The effects of aseptic production technology cover both employees and environment. Maspex Group has improved its competitiveness along with ensuring high quality products and more advantages for consumers of juice.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 225-235